52.7k views
3 votes
4(x - 3) = 4(2x + 1)

User Kassprek
by
5.8k points

2 Answers

4 votes

Answer:

x=-4

Explanation:

or 4*×-4*3=4*2x+4*1

or 4x-12=8x+4

or 4x-8x=4+12

or -4x=16

or x=16/-4

or =x=-4

User Clklachu
by
5.9k points
2 votes

Hi there! :)

Answer:


\huge\boxed{x = -4}

4(x - 3) = 4(2x + 1)

Distribute the coefficient outside of the parenthesis:

4(x)+ 4(-3) = 4(2x) + 4(1)

Simplify:

4x - 12 = 8x + 4

Subtract 4x from both sides:

4x - 4x - 12 = 8x - 4x + 4

-12 = 4x + 4

Subtract 4 from both sides:

-12 -4 = 4x + 4 - 4

-16 = 4x

Divide both sides by 4:

-16/4 = 4x/4

x = -4.

User Cordialgerm
by
5.7k points